2022
DOI: 10.1111/apt.16868
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: the importance of utilising gastrointestinal ultrasound via transperineal approach in ulcerative colitis—an accurate early predictor of response to treatment

Abstract: LINKED CONTENT This article is linked to Sagami et al papers. To view these articles, visit https://doi.org/10.1111/apt.16817 and https://doi.org/10.1111/apt.16895

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…We appreciate Dr Ardalan's and Dr Freidman's insightful editorial 1 on our publication, which showed that improvement in rectal bowel wall thickness (ΔrBWT) assessed by transperineal ultrasonography (TPUS) at 1 week post-induction therapy predicts subsequent clinical remission of ulcerative colitis (UC). 2 We agree that the clinical application of our findings may depend on the accuracy of the measurement of rBWT.…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 99%
See 1 more Smart Citation
“…We appreciate Dr Ardalan's and Dr Freidman's insightful editorial 1 on our publication, which showed that improvement in rectal bowel wall thickness (ΔrBWT) assessed by transperineal ultrasonography (TPUS) at 1 week post-induction therapy predicts subsequent clinical remission of ulcerative colitis (UC). 2 We agree that the clinical application of our findings may depend on the accuracy of the measurement of rBWT.…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 99%
“…To view these articles, visit https://doi.org/10.1111/apt.16817 and https://doi. org/10.1111/apt.16868 Shintaro Sagami 1,2 Taku Kobayashi 1 1…”
Section: N K Ed Co Ntentmentioning
confidence: 99%